Undergraduate translation teaching: a pedagogical perspective - Shehab, Ekrema; Ahmad Thawabteh, Mohammad (Onomázein, 2020)
In institutions across the world, translation training is accorded sacrosanct status in translation studies. Recent developments in translation and technology, combined with the increasingly prominent role of translation in the global marketplace, have given the discipline a renewed significance both academically and culturally. In Palestine, however, translator training has for many years subsisted on limited resources, despite the fact that translation, in most Palestinian universities English departments, has been a requisite course in English language and literature degrees at undergraduate level for the past four decades. Drawing on first-hand experience from teaching undergraduate translation courses at Al-Quds University and An-Najah National University, what this article attempts to investigate, then, is the status of translation teaching at the undergraduate level at English departments in Palestinian universities. To that effect, the paper uses a selective body of authentic translation examples and outlines some important issues which are indispensable to undergraduate translation teaching. The study offers advice and guidelines to university professors and instructors who do not have degrees and/or training in translation and find themselves obliged to teach undergraduate translation courses at their respective English departments.